Pola Persebaran dan Potensi Mata Air di Bentuk Lahan Karst di Kecamatan Giriwoyo Kabupaten Wonogiri - Yusuf, Muhammad; , Dra. Alif Noor Anna, M.Si; , Drs. Munawar Cholil, M.Si (2015)
ABSTRACT This research was conductedin The Sub DistrictGiriwoyo Distric ofWonogiriwhich aimstodescribe thespread ofthe springsas well asclassifyingthe qualityandquantity ofspringsfordrinkingwater supplyin the districtpopulationSub DistrictGiriwoyo Distric ofWonogiri.The method usedin this study isa surveyand laboratory testing. The data usedin this study consistedofprimary dataandsecondary data. Primary dataincludephysical parameters, chemical parameters, bacteriologicalparameters. As for thesecondary dataincludes dataof rainfall, administrativemaps, geologicalmaps, andmapsof land use, the dataobtainedfrom therelevant agencies. Water samplingis donewithpurposiverandom samplingmethod, as for considerationincludethe existence ofspringsusedin eachclass areaof karst areas, locationsspringsare usedfor the needs ofthe populationof eachvillagewill be takenonesamplesprings. The number of samplestaken8, hereinafterwater samplesanalyzedinthe laboratory to determinethe content ofthe elementsof physics, chemistry, andbakterilogi. Wateranalysis resultscompared withwater quality standardsfor drinking water. The research results show class II springs to discharge between 0.2 to 14.3 liters / sec, average quality already meet the standards, not only in Giriwoyo that due to its chemical properties, especially the pH 6.2 including low because under the minimum quality standard 6,5- magnitude 8.5, and total coliform (1100 / 100ml) is still above the maximum limit. For class III all the springs have to meet the standards and debit springs that exist between 2 to 3.1 liters / sec. Classification of the discharge area of research there are 3 classes. Class 4 with a discharge range (10 ≤ X <100) liters / sec have good water quality for drinking water. Class 5 with a discharge (1 ≤ X <10) liters / sec which has good water quality for drinking water, while the region Giriwoyo poor water quality because the content of pH below the minimum limit (6.2) and total colliform above the maximum limit ( 1100 / 100ml). Class 6 with a small discharge range (0.1 ≤ x <1) liter / sec have good water quality.